A performance evaluation index for two-phase thermosyphon loop used in HVAC systems. (25th February 2018) - Zhang, Penglei; Shi, Wenxing; Li, Xianting; Wang, Baolong; Zhang, Guohui
Highlights: A performance evaluation index of two-phase thermosyphon loop was proposed. Real cycles under different conditions were measured and evaluated. The performance of the "ideal cycle" is the upper limit of all real cycles. Reasons for lower approaching degree have been identified and illustrated visually. Ideal cycle can be approached with optimal charge and height difference, no flow drag. Abstract: For energy conservation, two-phase thermosyphon loops (TPTLs) have been widely used in air conditioning systems. Unfortunately, the evaluation index and design criterion of the TPTL is currently lacking, and causes for poor performance are inconclusive. In this study, an "ideal cycle" (optimal state) of the TPTL was proposed, and an approaching degree ε was defined to evaluate the extent of approaching the "ideal cycle". Furthermore, a visual experimental platform was developed, and real cycles under different conditions were measured and evaluated. The results indicate that: (1) the performance of the "ideal cycle" is the upper limit of the performances of all real cycles, and the approaching degree provides an effective evaluation index and design criterion; (2) causes for low approaching degree have been identified and illustrated visually, from the perspective of refrigerant distribution, including under-charged refrigerant, over-charged refrigerant, insufficient height difference, and considerable flow resistance; and (3) the "ideal cycle" can be approached, only when the filling ratio (100%) and the height difference (1.2 m) is optimal, and the flow resistance is negligible simultaneously.